2008
DOI: 10.1002/tox.20459
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanoic acid alters T lymphocyte phenotypes and cytokine expression in mice

Abstract: Perfluorooctanoic acid (PFOA) has been used in commercial applications and detected in environmental matrices. This study focuses on whether PFOA affects the function of immune organs (spleen and thymus). Male ICR mice were exposed to 0, 2, 10, 50, and 250 ppm of PFOA in drinking water for 21 days. PFOA differently altered T lymphocyte populations. In the spleen, all doses of PFOA decreased CD8(+) lymphocytes; CD4(+) lymphocytes were increased by 50 and 250 ppm of PFOA. Exposure to 250 ppm of PFOA increased CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 34 publications
(44 reference statements)
1
33
0
Order By: Relevance
“…Hepatomegaly is often associated with chronic inflammatory liver disease. The liver is the major metabolizing organ and it is targeted following PFC exposure (28). Previous findings have shown that exposure to PFCs caused various chronic abnormalities, including hepatocellular hypertrophy and hepatomegaly (29,30).…”
Section: Pfc Exposure Alters Tissue-specific Mrna Expression In Vivomentioning
confidence: 99%
“…Hepatomegaly is often associated with chronic inflammatory liver disease. The liver is the major metabolizing organ and it is targeted following PFC exposure (28). Previous findings have shown that exposure to PFCs caused various chronic abnormalities, including hepatocellular hypertrophy and hepatomegaly (29,30).…”
Section: Pfc Exposure Alters Tissue-specific Mrna Expression In Vivomentioning
confidence: 99%
“…20 Monoclonal antibodies were conjugated with fluorescein isothiocyanate ([FITC] emission at 525 nm) or phycoerythrin ([PE] emission at 575 nm). Antibodies to cell-specific receptors (Sasnta Cruz Biotechnology, Santa Cruz, CA, USA) included hamster anti-mouse CD3-FITC (T lymphocyte), rat anti-mouse CD45R/B220-PE (B lymphocyte), rat anti-mouse CD4-FITC (T helper lymphocyte), and rat anti-mouse CD8-PE (T cytotoxic/ suppressor lymphocyte).…”
Section: Phenotyping Of Splenic and Thymic Lymphocytesmentioning
confidence: 99%
“…Exposure of laboratory animals to PFOA and PFOS has resulted in hepatomegaly, hepatic peroxisome proliferation, atrophy and alteration of cell populations in lymphoid organs (Yang et al 2000;Qazi et al 2009;Son et al 2009;DeWitt et al 2012;Dong et al 2012), suppression of the T-cell-dependent IgM antibody response (TDAR), alterations in inflammatory cytokine signaling (Peden-Adams et al 2008;Zheng et al 2009Zheng et al , 2011Dong et al 2011;DeWitt et al 2012), and reduction in thyroid hormone levels (Curran et al 2008). PFOS reduced the host resistance to influenza A virus and natural killer cell activity in B 6 C 3 F 1 mice (Guruge et al 2009).…”
Section: Introductionmentioning
confidence: 99%